2016
DOI: 10.1038/bjc.2015.471
|View full text |Cite
|
Sign up to set email alerts
|

Cell line and patient-derived xenograft models reveal elevated CDCP1 as a target in high-grade serous ovarian cancer

Abstract: Background:Development of targeted therapies for high-grade serous ovarian cancer (HGSC) remains challenging, as contributing molecular pathways are poorly defined or expressed heterogeneously. CUB-domain containing protein 1 (CDCP1) is a cell-surface protein elevated in lung, colorectal, pancreas, renal and clear cell ovarian cancer.Methods:CUB-domain containing protein 1 was examined by immunohistochemistry in HGSC and fallopian tube. The impact of targeting CDCP1 on cell growth and migration in vitro, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 58 publications
2
63
0
Order By: Relevance
“…In this study, we found HAX1, RAB1B, PBX3, CDCP1 and PLAGL2 to be direct miR-654 targets, and their silencing revealed that the miR-654-related phenotype in OC is primarily caused by direct targeting of CDCP1 and PLAGL2 oncogenes. Furthermore, CDCP1 and PLAGL2 levels were found to be increased in ovarian tumors compared to normal samples, which has also been seen in leukemia [35] for PLAGL2, and in other malignancies including OC [36,37] for CDCP1, supporting their role in OC progression and turning them into attractive therapeutic targets.…”
Section: Discussionmentioning
confidence: 67%
“…In this study, we found HAX1, RAB1B, PBX3, CDCP1 and PLAGL2 to be direct miR-654 targets, and their silencing revealed that the miR-654-related phenotype in OC is primarily caused by direct targeting of CDCP1 and PLAGL2 oncogenes. Furthermore, CDCP1 and PLAGL2 levels were found to be increased in ovarian tumors compared to normal samples, which has also been seen in leukemia [35] for PLAGL2, and in other malignancies including OC [36,37] for CDCP1, supporting their role in OC progression and turning them into attractive therapeutic targets.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, CDCP1's role in tumor metastasis was confirmed in vivo in lung (15,16), ovarian (17), prostate (5), and colon (9) cancers. Although CDCP1's role in TNBC metastasis has not been established to date, high CDCP1 expression has been validated as a prognostic marker of poor survival in TNBC when combined with positive node status (18).…”
mentioning
confidence: 87%
“…It is expressed by epithelial cells of most organs [1][2][3] and its over-expression is associated with poor survival of patients with renal cell carcinoma [4,5], colorectal [6], lung [7,8], pancreatic [9], and breast cancer [10], and clear cell ovarian carcinoma [11]. CDCP1 modulates adhesion and promotes motility of cells in vitro [2,9,[12][13][14], mediates metastasis in in vivo models [11,12,[14][15][16][17], and also contributes to in vitro and in vivo resistance of cancer to chemotherapy [11,17] and targeted agents [10,18,19].…”
Section: Introductionmentioning
confidence: 99%